EPISTEMOLOGI PENDIDIKAN ISLAM: STRATEGI PENANAMAN KARAKTER DI SEKOLAH DASAR ISLAM INTERNASIONAL NURUL MUSTHOFA KLATEN - Muhammad Badruddin Zarkasyi; Mujiburrohman (LPPM STAI Muhammadiyah Probolinggo, 2026)
Character education is a fundamental element of the educational process because it plays a vital role in shaping students' superior personalities, not only on an intellectual level but also in the moral and spiritual dimensions. From an Islamic educational perspective, character education has a strategic position because it is oriented towards the internalisation of Islamic values ​​based on monotheism and noble morals. This study aims to analyse the concept of Islamic educational epistemology in the strategy of character building for students at the elementary school level, with a focus on the study at the Nurul Musthofa International Islamic Elementary School (SDII) in Klaten, and to examine the impact of its implementation on student character development. This study uses a qualitative method with a descriptive approach. Research data were obtained through direct interviews with teachers at SDII Nurul Musthofa in Klaten and supported by documentation studies from various relevant literature sources, such as books, journals, and scientific articles. The results of the study indicate that Islamic educational epistemology plays a significant role in shaping students' character through the implementation of school programs integrated with the values ​​of monotheism, moral development, and social responsibility. An educational environment built on these values ​​can create a conducive school culture and support the holistic development of student character. This research confirms that the application of the epistemological principles of Islamic education, particularly through role-modelling and habituation strategies, makes a significant contribution to student character development and has practical implications for Islamic educational institutions in building a values-based education system.